Studies in Consumer Demand (vol.1) - Islam, Nurul (Dacca Bureau of Economic Research, Dacca University, 1965)
An analysis of family budgets of industrial workers in East Pakistan.
Include Statistical Appendix.
Prof. Nurul Islam was Head of Department of Economics, Dacca University.
Keywords: Pakistan -- Consumers